Mobile Application Based Rehabilitation for hand Functions in Parkinsonism: A Review (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Parkinson's disease is the most common neuro-degenerative disease. Diagnosis, assessment as well as treatment of these patients, on the other hand, is a complex process that necessitates constant monitoring. Mobile phones are helpful in control of this disease in this context.Objective: Goal is to conduct a standard study on use of mobile applications in this disease .Materials and methods: Study of the literature for articles announced in English between 2010 to 2015 that analysed , validated apps especially planed for and conveniant in Parkinson's disease. We also searched the leading app stores for apps that could be useful for Parkinson's disease patients.Conclusions: The app and literature searches gives a total of 125 apps, 55 are classified as potentially convenient in this disease , 70 were practically planed for this disease. A number of apps are potentially convenient in or partically planned for Parkinson's disease management. Though, medical confirmation supporting these utility is limited and bad nature. More research is required to confirm the device and control their use.